Flower Pollination Algorithm (FPA) to Solve Quadratic Assignment Problem (QAP) - Derby Prayogo Samdean; Herry Suprajitno; Edi Winarko (Universitas Airlangga, 2019)
The purpose of this paper is to solve Quadratic Assignment Problem using Flower Pollination Algorithm. Quadratic Assignment Problem discuss about assignment of facilities to locations in order to minimize the total assignment costs where each facility assigns only to one location and each location is assigned by only one facility. Flower pollination Algorithm is an algorithm inspired by the process of flower pollination. There are two main steps in this algorithm, global pollination and local pollination controlled by switch probability. The program was created using Java programming language and implemented into three cases based on its size: small, medium and large. The computation process obtained the objective function value for each data using various values of parameter. According to the pattern of the computational result, it can be concluded that a high value of maximum iteration of the algorithm can help to gain better solution for this problem.